Present situation of contagious bovine pleuropneumonia in Central African Republic - (:unkn) unknown (My University, 2021)
Aims. The aim of this study was to analyse the current situation of Contagious Bovine Pleuropneumonia (CBPP) in the Central African Republic (CAR) by seroprevalence analysis, as well as isolation and characterization of strains of the etiologic agent, Mycoplasma mycoides mycoides (Mmm), circulating in livestock breeding regions. Material and methods. The strains obtained were subjected to whole genome sequencing by Illumina technology and genotyped using the eMLST technique based on 62 genes of the Mmm core genome. Their sensitivity to tetracycline was assessed by determination of the minimum inhibitory concentration (MIC) on agar. A seroprevalence analysis by competitive ELISA was conducted in livestock breeding regions (West, Centre and East CAR), including both zebu and taurine cattle breeds, and both males and females. Results. The three strains isolated in the three regions of the CAR shared exactly the same genomic sequence. Phylogenetic analysis showed that they were closely related to a strain isolated in the CAR in 1991, also sequenced in this study, and clustered with Mmm strains originating from East and Central Africa. The recent isolates presented increased MIC values, though they were still sensitive to tetracycline. The global CBPP prevalence in the CAR was estimated at 12.5% with no significant differences observed between cattle breeding regions, nor between males and females. However, a significantly higher prevalence was observed in zebu compared to taurine cattle, most likely in relation to their herding system based on cattle transhumance and nomadic pastoralism. Conclusion. CBPP is enzootic in the CAR in spite of control campaigns based on use of the live T1 vaccines, which have shown little efficacy due to poor implementation in the field. New strategies combining controlled use of antibiotics and inactivated vaccines, with increased thermostability, should be well received by livestock keepers and allow a better control of CBPP
Keywords: African Research